Beyond nosology? Molecular tumor boards, singularization, and the conflation of diagnosis and therapy. Issue 1 (2nd January 2021) - Cambrosio, Alberto; Campbell, Jonah; Bourret, Pascale
Abstract : This article partakes in a number of recent attempts to map the reconfiguration of clinical work as part of the deployment of precision oncology. We focus on the platforms, in particular Molecular Tumor Boards, that act as a condition of possibility for implementing innovative experimental interventions, and which are part of the emergence, beyond the traditional confines of diagnosis, of a data "ecosystem" geared towards increasing patient access to drugs matched to their genomic profile. MTBs are a key component of this singularization process, and their activities are central to the looping mechanisms that connect the diagnosis of individual patients to the revision of diagnostic categories. These categories are no longer "merely" diagnostic but operate as predictive guides to therapy.